Ironi Ayub, Ironi Yesus: Re-Evaluasi Fungsi Dialog Tuhan-Satan dalam Prolog Kitab Ayub - Randy Frank Rouw (Jurnal Kala Nea, 2025)
Several scholars argue that the dialogue between God and Satan in the prologue of the Book of Job can be omitted without consequence, suggesting that the narrative of suffering remains coherent even without this conversation. However, this article contends that this dialogue possesses crucial theological and narrative functions. Using a qualitative approach with textual analysis methods, this research comprises four integrated stages: (1) lexical analysis of Hebrew text to identify key terms such as tam, ?inn?m, and 'avdi; (2) narrative-ironic analysis that integrates the function of frame narrative and dramatic irony; (3) intertextual analysis connecting the dialogue with the tradition of the Suffering Servant (Isaiah 40–55) and Christ's suffering; and (4) synthesis of all four analyses. The findings demonstrate that the God-Satan dialogue creates essential dramatic irony that provides divine perspective to readers, builds the theme of "suffering without cause" (?inn?m), establishes Job's status as "my servant" ('avdi), and forms typological patterns linking Job to Christ. This dialogue is not a dispensable narrative element but a hermeneutical foundation that opens understanding of the irony of righteous suffering and the Christological typology in the Book of Job.